2005
DOI: 10.1108/02644400510619530
|View full text |Cite
|
Sign up to set email alerts
|

Predictor‐corrector procedures for pseudo‐dynamic tests

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…See also [5], [51], or [52] for good overviews of numerical time integration algorithms in hybrid testing.…”
Section: Accuracy and Stability Of Hybrid Testing -Time Integration Tmentioning
confidence: 99%
See 2 more Smart Citations
“…See also [5], [51], or [52] for good overviews of numerical time integration algorithms in hybrid testing.…”
Section: Accuracy and Stability Of Hybrid Testing -Time Integration Tmentioning
confidence: 99%
“…The scheme was developed in order to combine the speed of computation from explicit methods with numerical dissipation. Nakashima & Kato, [72] proposed an error compensation technique called the I-Modification that required the predictor stiffness of the structure and the difference between measured and command displacements [51]. Bursi and Shing, [65] showed that its use with the α-OSM mitigates the effects of undershoot type experimental errors by introducing energy dissipation.…”
Section: Operator-splitting Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the direct integration methods were developed for pure analytical solutions and not necessarily suitable for HS tests (Schellenberg et al, 2009b). Because of this need, one of the main focuses of HS/RTHS research has been to develop numerical integration algorithms that are specialized to solve the substructured equation of motion in HS to have accurate and reliable test results (e.g., Chang, 2002;Bonelli and Bursi, 2005;Chen et al, 2009;Kolay and Ricles, 2014). However, the developed HS-specific methods have still some challenges and limitations, particularly for complex and large analytical substructures with many degrees of freedoms and/or large non-linearities.…”
Section: Introductionmentioning
confidence: 99%
“…2,3]. Key improvements include the development of robust numerical integration techniques [4] and effective delay compensation approaches [5], the implementation of geographically distributed hybrid simulations [6,7], and the development of force based control methods [8]. Past studies focused on the accuracy, stability and reliability of the hybrid method and only a few tests examined the response of structures in which hybrid simulation is used as a seismic test method.…”
Section: Introductionmentioning
confidence: 99%